2007
DOI: 10.1055/s-2007-985901
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Gingival Hyperplasia in a Neonate with Foetal Valproate Syndrome

Abstract: There are several causes of gingival hyperplasia and one of the most well-known is drug-induced gingival enlargement. Nevertheless, causes of congenital gingival enlargement include only hereditary and metabolic disorders. Only one case of drug-induced congenital gingival hyperplasia has been reported. We present the second neonate with gingival hyperplasia in the context of foetal valproate syndrome and review the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A congenital case has been described in a child exposed to valproic acid in utero. [26] Vigabatrin is a relatively new antiepileptic agent that can also cause gingival overgrowth. Immunohistochemical study suggested that vigabatrin induced an increase in epithelial cell proliferation due to overexpression of antigen Ki-67 and slight underexpression of the CDK-inhibitors p27 KIP1 and p21 WAF1 .…”
Section: Drugs Which Cause Gingival Overgrowthmentioning
confidence: 99%
“…A congenital case has been described in a child exposed to valproic acid in utero. [26] Vigabatrin is a relatively new antiepileptic agent that can also cause gingival overgrowth. Immunohistochemical study suggested that vigabatrin induced an increase in epithelial cell proliferation due to overexpression of antigen Ki-67 and slight underexpression of the CDK-inhibitors p27 KIP1 and p21 WAF1 .…”
Section: Drugs Which Cause Gingival Overgrowthmentioning
confidence: 99%
“…Reported cases of gingival enlargements were induced by different drugs; CCBs (50/119 – of which amlodipine-25;[8910111213141516171819202122232425262728] nifedipine-13;[26293031323334353637383940] verapamil-4;[41] felodipine-2;[4243] nisoldipine-1;[44] manidipine-1;[45] and unspecified CCBs-4[46]); phenytoin (11/119);[4748495051525354555657] cyclosporine (31/119);[3546585960616263646566676869707172737475] phenobarbital (4/119);[767778] sodium valproate (3/119 - including one report of congenital drug-induced gingival hyperplasia);[798081] d-penicillamine (2/119);[82] combination oral contraceptive pill-lynestrenol and ethinyl estradiol (1/119);[83] vigabatrin (1/119). [84] Cases of gingival enlargement after combination drug therapy have also been reported; a combination of cyclosporine and CCBs (11/119);[354685...…”
Section: Resultsmentioning
confidence: 99%
“…The etiology of the patient's gingival hyperplasia remains unknown. With no family history and no apparent association with any medical syndromes, the impression is that the gingival hyperplasia is idiopathic in nature and possibly exacerbated by some drug influence from divalproex sodium, which has been reported to have controversial effects on gingival tissues [6, 1316]. It could also be a rare mutation or other hereditary disorder with some variance in expression such that other family members are not affected.…”
Section: Discussionmentioning
confidence: 99%
“…Rare cases of sodium valproate-related gingival enlargement have also been reported, including one involving infantile gingival overgrowth at birth secondary to maternal sodium valproate use [1316]. However, a clinical study involving epileptic adults receiving sodium valproate and a control group showed no significant differences between the two groups on any parameters assessed [6].…”
Section: Introductionmentioning
confidence: 99%